VALUASI EKONOMI : STUDI BIBLIOMETRIK VOSVIEWER - I Wayan Priyana Agus Sudharma (Nusantara Hasana Journal, 2024)
The aim of this research is to determine the development of research related to economic valuation. This analysis attempts to put a price on each natural resource and environmental input to the economy, including estimating the price of inputs not typically included in market transactions, such as clean air and water. The research was conducted using the Crossref database from 1990 to 2023. The results of the study show that the development of scientific publications on the topic is experiencing an increasing trend. From 2012 to 2016, the study topic discussed dominant terms in relation to other terms such as Biodiversity, Development, Market, Risk, and Economic Value, Willingness. After 2016, published articles discussed more about Companies and Ecosystem Services. Articles with the keywords Ecosystem Service, Biodiversity, and Environment show relatively dark colors so that this topic still has a big opportunity to be researched.